2014
DOI: 10.1159/000363691
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Sepsis with Multi-Organ Failure and Treated with a New Dialysis Device Specifically Designed for Newborns

Abstract: Neonatal sepsis due to E. coli is often complicated by multiple organ failure (MOF) and a high mortality risk. We report the case of a term newborn discharged in good condition who suddenly fell into septic shock after 11 days and required immediate resuscitation, volume expansion and a high-dosage amine infusion. Extremely severe metabolic acidosis, disseminated intravascular coagulation (DIC) with diffuse bleeding, and unstable hemodynamic status with oliguria turned into strict anuria, and the patient becam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…A specialized pediatric CRRT circuit, the PrismaFlex HF20, with an extracorpeal volume of 60 ml [ 26 ] is currently being tested for FDA approval at pediatric centers throughout the USA. CARPEDIEM is RRT equipment with a 27 ml extracorpeal circuit volume and capability to handle blood flow rates 5–50 ml/hr., that once approved should dramatically improve the mechanics of treating the smallest patients [ 27 , 28 ]. Additionally, the Newcastle infant dialysis and ultrafiltration system (NIDUS) is hemodialysis equipment designed for use in infants 800 g to 8 kg, without need for blood priming as well as using only single lumen vascular access, and successful use has been published on 9 babies weighing 1.8 kg to 5.9 kg in the United Kingdom [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A specialized pediatric CRRT circuit, the PrismaFlex HF20, with an extracorpeal volume of 60 ml [ 26 ] is currently being tested for FDA approval at pediatric centers throughout the USA. CARPEDIEM is RRT equipment with a 27 ml extracorpeal circuit volume and capability to handle blood flow rates 5–50 ml/hr., that once approved should dramatically improve the mechanics of treating the smallest patients [ 27 , 28 ]. Additionally, the Newcastle infant dialysis and ultrafiltration system (NIDUS) is hemodialysis equipment designed for use in infants 800 g to 8 kg, without need for blood priming as well as using only single lumen vascular access, and successful use has been published on 9 babies weighing 1.8 kg to 5.9 kg in the United Kingdom [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Partly responsible for the increase is that diseases that previously had high fatality rates, such as sepsis, congenital heart disease, and certain cancers, have increased survival due to increased quality of care [46]. The functional consequence of AKI is reduced glomerular filtration rate.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that after 24 h of CRRT, the levels of blood urea nitrogen and creatinine decreased significantly. In 2016, when the demand for metabolism and fluid management exceeds the capacity of kidney, which is called fluid overload, it should be treated as early as possible [24]. This means that when the metabolism and fluid management of sepsis-related AKI are beyond the renal capacity, (even without renal damage), CRRT should be initiated in time.…”
Section: Discussionmentioning
confidence: 99%